2021
DOI: 10.17219/acem/133426
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the promoter methylation of PHF20L1 and the gene association with metastasis in breast cancer

Abstract: Hernandez-Caballero ME. An insight into the promoter methylation of PHF20L1 and the gene association with metastasis in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Another histone demethylase PHF8 promoted EMT and breast tumorigenesis ( 140 ). PHF20L1, a methyl lysine reader protein containing a TUDOR domain, plays important role in breast cancer metastasis ( 141 ). Studies suggested its oncogenic role in response to hypoxic conditions, where it facilitated glycolysis, cell growth and metastasis of breast cancer cells by exerting its direct inhibitory activities on certain genes of tumor suppressive nature like HIC1 , KISS1 , and BRCA1 ( 142 ).…”
Section: Epigenetic Players In Breast Cancermentioning
confidence: 99%
“…Another histone demethylase PHF8 promoted EMT and breast tumorigenesis ( 140 ). PHF20L1, a methyl lysine reader protein containing a TUDOR domain, plays important role in breast cancer metastasis ( 141 ). Studies suggested its oncogenic role in response to hypoxic conditions, where it facilitated glycolysis, cell growth and metastasis of breast cancer cells by exerting its direct inhibitory activities on certain genes of tumor suppressive nature like HIC1 , KISS1 , and BRCA1 ( 142 ).…”
Section: Epigenetic Players In Breast Cancermentioning
confidence: 99%